Does moderate intensity exercise in the postprandial period attenuate the inflammatory response to a high-fat meal? - Teeman, Colby S. (Kansas State University, 2015)
Background: High-fat meals (HFM) have been shown to increase postprandial lipemia (PPL) and inflammation. Acute exercise both pre and post-meal has been shown to attenuate PPL and inflammation. However, studies examining the interaction of HFMs and exercise on PPL and inflammation have used meal and exercise conditions more extreme than typical for average adults. The purpose of this study was to determine if moderate intensity exercise following a "true-to-life" HFM would attenuate PPL and inflammation. Methods: Participants were thirty-nine young adults (18-40 years) with no known metabolic disease. Inclusion criteria consisted of participants meeting physical activity guidelines of ≥ 150 min/week of moderate-to-vigorous physical activity or ≥ 75 min/week of vigorous activity, or < 30 min of planned physical activity per week. Participants were block randomized to EX or CON groups. Participants consumed a HFM of 10 kcal/kgbw. The EX group walked at 60% VO[subscript 2peak] to expend ≈ 5 kcal/kgbw beginning one-hour following the HFM. The CON group remained sedentary during the postprandial period. Blood samples were collected at baseline and 2, and 4hrs postprandially. Results: At baseline, there were no differences between EX and CON groups for any metabolic or inflammatory markers (p>0.05). Postprandial TRG increased ≈ 100% (p<0.001) in both groups, with no differences between groups. HDL concentrations decreased across time in both groups (p<0.001) with no differences between groups (p=0.338). HDL was higher in the EX group at 2hrs (p=0.047), but not 4hrs (p=0.135). IL-6 and TNF-α concentrations did not change over time with no differences between groups (p>0.05). The EX group increased sVCAM-1 from baseline to 4hr (p=0.003), while the CON group did not. Change in TRG was associated with change IL-6, IL-8, IL-10 and TNF-α from baseline to 2hrs when controlling for VO[subscript 2peak] and body fat%. No other associations were seen between change scores for TRG and inflammatory markers. Conclusions: Despite significant increases in PPL following a HFM, moderate intensity exercise in the postprandial period did not mitigate the PPL nor the inflammatory response to the HFM. These results indicate PPL and inflammation following a HFM are not directly related in a young, healthy population with low metabolic risk.
Keywords: Postprandial lipemia; High-fat meal; Inflammation; Aerobic exercise